2022
DOI: 10.3390/biom12010101
|View full text |Cite
|
Sign up to set email alerts
|

HMGB1 Inhibition to Ameliorate Organ Failure and Increase Survival in Trauma

Abstract: Several preclinical and clinical reports have demonstrated that levels of circulating high mobility group box 1 protein (HMGB1) are increased early after trauma and are associated with systemic inflammation and clinical outcomes. However, the mechanisms of the interaction between HMGB1 and inflammatory mediators that lead to the development of remote organ damage after trauma remain obscure. HMGB1 and inflammatory mediators were analyzed in plasma from 54 combat casualties, collected on admission to a military… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 70 publications
(98 reference statements)
3
22
0
Order By: Relevance
“…Emerging evidence shows that acute liver failure patients/animals have high concentrations of circulating HMGB1, which can contribute to multiple organ injuries and mediate gut bacterial translocation [ 13 ]. A recent observational study by Yang et al further found significantly increased plasma concentrations of HMGB1 in combat casualties on arrival to the hospital correlated positively with blood inflammatory mediators [ 44 ]. An in vivo study showed that CX-01 (2-O,3-O-desulfated heparin) with < 5% anticoagulant activity significantly inhibited systemic HMGB1 activity, decreased local and systemic inflammatory responses, and reduced tissue and organ damage in a blast injury-induced trauma rat model [ 44 ].…”
Section: Overview Of the Immunopathological Roles Of Hmgb1 And Histon...mentioning
confidence: 99%
See 1 more Smart Citation
“…Emerging evidence shows that acute liver failure patients/animals have high concentrations of circulating HMGB1, which can contribute to multiple organ injuries and mediate gut bacterial translocation [ 13 ]. A recent observational study by Yang et al further found significantly increased plasma concentrations of HMGB1 in combat casualties on arrival to the hospital correlated positively with blood inflammatory mediators [ 44 ]. An in vivo study showed that CX-01 (2-O,3-O-desulfated heparin) with < 5% anticoagulant activity significantly inhibited systemic HMGB1 activity, decreased local and systemic inflammatory responses, and reduced tissue and organ damage in a blast injury-induced trauma rat model [ 44 ].…”
Section: Overview Of the Immunopathological Roles Of Hmgb1 And Histon...mentioning
confidence: 99%
“…A recent observational study by Yang et al further found significantly increased plasma concentrations of HMGB1 in combat casualties on arrival to the hospital correlated positively with blood inflammatory mediators [ 44 ]. An in vivo study showed that CX-01 (2-O,3-O-desulfated heparin) with < 5% anticoagulant activity significantly inhibited systemic HMGB1 activity, decreased local and systemic inflammatory responses, and reduced tissue and organ damage in a blast injury-induced trauma rat model [ 44 ]. Many studies have claimed a positive correlation between extracellular HMGB1 and severe acute pancreatitis (SAP) severity in recent decades [ 15 ].…”
Section: Overview Of the Immunopathological Roles Of Hmgb1 And Histon...mentioning
confidence: 99%
“…IRI and tissue damage after TH activates a complement cascade that plays a crucial role in inflammation-driven MODS [ 43 ]. Our previous findings showed early systemic/tissue complement activation associated with multiple-organ damage in rat and porcine models of TH [ 6 , 13 , 14 , 21 , 22 , 23 , 38 ]. Consistent with the previous findings, this study also demonstrated that increased generation and deposition of C3, C5a, and C5b-9 were associated with acute lung and intestinal injury, suggesting that early immunological damage control approaches aim to modulate TH-induced complement activation and thus may change TH management procedures to improve outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies have shown the favorable effects of pharmacological targeting of complement as evidenced by improved hemodynamics, decreased organ damage, modulation of inflammatory responses, reduced fluid requirements, and increased survival in rats and swine with traumatic hemorrhage [ 14 , 20 , 21 ]. Our clinical and animal studies also showed a direct correlation between complement activation and outcomes in the setting of traumatic hemorrhage [ 22 , 23 ].…”
Section: Introductionmentioning
confidence: 87%
“…A thorough review presented by Jennifer F. Kugel and collaborators [ 5 ] summarizes recent advances in our understanding of the interactions of HMGB proteins with the genome and the impact on disease. Finally, the paper by Yansong Li and collaborators shows the correlation between blast injury and an early increase in HMGB1 plasma levels, along with severe tissue damage and high mortality; and the role of 2-O, 3-O desulfated heparin to inhibit local and systemic inflammatory responses [ 6 ].…”
mentioning
confidence: 99%